The competitive advantage of getting tender: a case study of United Engineers Malaysia Berhad / Nurul Azwa Ismail - Ismail, Nurul Azwa (2010)
This case study explored the criteria used by United Engineers Malaysia Berhad (UEM) and also their competitors in terms of getting into tender. UEM has their own competitive advantage which is their subsidiaries. A competitive advantage exists when the firm is able to deliver the same benefits as competitors but at a lower cost, or deliver benefits that exceed those of competing products. The main issue is either the competitive advantage that UEM have can help them to get the tender compared to other competitors. This issue deeply explained in the report in order to be more clarifying for understanding of criteria to get into tender. Some of the suggestions have been explained to make sure UEM concern more about their competitive advantage.